2009
DOI: 10.4103/0974-1208.57224
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hCG 3D and 3D power Doppler assessment of the follicle for improving pregnancy rates in intrauterine insemination cycles

Abstract: BACKGROUND:The assessment of follicular maturity at the time of human chorionic gonadotropin (hCG) is one of the key factors for the success of all assisted reproductive techniques.AIM:To assess follicles by three dimensional (3D) and 3D power Doppler (PD) before giving hCG to improve pregnancy rates in intrauterine insemination (IUI) cycles.DESIGN:Prospective randomized study.MATERIALS AND METHODS:Ultrasound for pre-hCG follicular assessment was performed over a period of 10 months for all 1000 cycles of IUI.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…3D and power Doppler ultrasound examination before giving hCG may help to assess more accurately follicular diameter and volume measurement and to identify the presence of cumulus. This will evaluate the parameters of perifollicular vascularity to ensure the presence of a mature ovum in the follicle that may improve pregnancy rates in intrauterine insemination cycles [32]. The follicular volume is higher in the anovulatory intrauterine insemination cycle [33].…”
Section: Ovulation Induction and Infertilitymentioning
confidence: 99%
“…3D and power Doppler ultrasound examination before giving hCG may help to assess more accurately follicular diameter and volume measurement and to identify the presence of cumulus. This will evaluate the parameters of perifollicular vascularity to ensure the presence of a mature ovum in the follicle that may improve pregnancy rates in intrauterine insemination cycles [32]. The follicular volume is higher in the anovulatory intrauterine insemination cycle [33].…”
Section: Ovulation Induction and Infertilitymentioning
confidence: 99%
“…However, they found that periovulatory subfollicular VI and VFI were lower in pregnant women [ 29 ]. Another study by Panchal and Nagori [ 30 ] showed that pregnancy rates were higher when the perifollicular RI was <0.50, and the PSV was >11 cm/s on the day of IUI trigger. Furthermore, they found that perifollicular VI values between 6 and 20 and a perifollicular FI >27 led to higher pregnancy rates [ 30 ].…”
Section: Ovarian Blood Flowmentioning
confidence: 99%
“…Another study by Panchal and Nagori [ 30 ] showed that pregnancy rates were higher when the perifollicular RI was <0.50, and the PSV was >11 cm/s on the day of IUI trigger. Furthermore, they found that perifollicular VI values between 6 and 20 and a perifollicular FI >27 led to higher pregnancy rates [ 30 ]. However, the findings remain controversial, and there are no definite references as to which vascularity parameters on the day of trigger increase the chances of pregnancy during IUI.…”
Section: Ovarian Blood Flowmentioning
confidence: 99%
“…Color Doppler is a high-throughput, sophisticated imaging technique for the assessment of uterine anomalies, intrauterine pathology, tubal patency, polycystic ovaries, ovarian follicular monitoring, endometrial receptivity, failed and/or ectopic pregnancy, male infertility, and uterine, endometrial, and ovarian vascularity 1-6 . Human chorionic gonadotropin (hCG) three dimensional power Doppler assessment of the follicle was implicated in improving pregnancy rates in intrauterine in seminal cycle 7 . Three dimensional volume reconstruction by the virtual organs computer-aided analysis (VOCL) technique allows ovarian volume calculation, and automatic volume calculation software provides the follicular count and mean volumetric calculation 8 .…”
Section: Overview Of Color Doppler In Infertilitymentioning
confidence: 99%